Birds and people: studies based on citizen science and census data of Greater Gauteng, South Africa - Wala, Zingfa Jantur (Department of Biological Sciences, 2019)
Global human population growth has been predicted to grow exponentially, to a point where it exceeds the capacity of available resources to sustain it. The consequences that such exponential increase will have on the environment has also been the focus of several research. The spatial pattern of human population has reveal uneven pattern of human population with the urban areas being subject of increased influx of human population from the rural areas in search of better economic factors. The United Nations in 2007 revealed that at least half of the world’s 6.6 billion human population was living in urban areas. This number is expected to increase to over 60% of the world's population by the end of 2050. Most of this population growth is occurring in developing countries. While the health, security and town planning amongst other consequences of this global explosion in urbanization have been well-studied and documented, the impact which urbanization is having and will have on the ecosystem and on biodiversity, especially at regional and local scales has remained an a field of knowledge that has continued to evolve especially given the variable patterns and drivers of urbanization in different regions of the world as well as the different environmental factors and biodiversity in these regions. Biodiversity monitoring has been shown to be crucial to conservation goals aimed at accessing the state and condition of biodiversity. The Second South African Bird Atlas Project (SABAP2) is a citizen science atlas project which commenced in 2007. Over a decade, SABAP2 has produced a rich source of data, capturing bird distributions in South Africa. This makes SABAP2 a powerful tool for monitoring observed changes in bird communities and by extension biodiversity through time. I examined the effect that urbanization is having on the avian biodiversity in South Africa, one of the most urbanized countries in Africa. My research was focused on the 576 pentads in the four one-degree grid cells (25S 27E, 25S 28E, 26S 27E and 26E 28E) centered on the Gauteng province, referred to as Greater Gauteng region. In addition to being very urbanized, Greater Gauteng is also the most populated area in the country, and is home to 30% of the country’s 51 million people. The region is the most atlased SABAP2 region in the country, with each pentad having a minimum of 11 full-protocol SABAP2 checklists. It thus provide opportunities for the development of tools to monitor the temporal dynamics of bird communities. The first chapter is the general introduction where I did an extensive literature review of the research subject and gave an overview of the data chapters that make up the thesis. In the second chapter, I examined spatial patterns of urbanization and avian biodiversity. I assess avian species composition in the urban and rural areas of Greater Gauteng. I categorized bird data from SABAP2 for Greater Gauteng Urban and Rural subgroups. The dataset for this chapter had 700 bird species. 644 showed no range preference for either urban or rural areas. Five species showed a preference for rural areas while 51 species showed a preference for urban areas. The higher species richness recorded in urban pentads highlights the often overlooked benefits of biodiversity conservation efforts in urban areas such as green spaces and parks, gardens and water bodies. This chapter highlights the need for conservation efforts to be targeted at birds and other biodiversity in urban spaces. It is also raises the need to further promote policies aimed at having conservation efforts incorporated into town planning. In the third and fourth chapters, I used data from SABAP2 to investigate how different protected areas such as Important Bird Areas (IBAs) are to their surrounding areas by demonstrating how different the Devon Grasslands (Chapter 3) and Suikerbosrand Nature Reserve (Chapter 4) IBAs are to their immediate surrounding areas in terms of avian species richness and assemblage. Atlas data from the pentads covering these two IBAs were compared with data from the surrounding pentads. Both IBAs stand out as having more bird species than their immediate surroundings. The simple yet effective method used in this chapters can be applied in identifying potential sites for biodiversity conservation. In the fifth chapter, using a variation of the Shannon-Weiner species diversity index which is known to reach an asymptote rapidly even while species richness keeps increasing, to investigate patterns of spatial distribution of species richness and proportional diversity in Greater Gauteng. The chapter provides insights into pentads with the richest bird communities and also provides a method which can be applied to citizen science data such as SABAP2 to discover areas where particular groups of species, such as waterbirds and threatened species, are concentrated in the region. The sixth chapter examines the relationship between reporting rates of birds and human population in Greater Gauteng. With Greater Gauteng being the most populated region in South Africa, it presented an ideal situation to investigate patterns of correlation between human population and the reporting rates of bird species in the region. Based on the results obtained, the species were grouped into 18 groups categorized by the relationship pattern revealed by species reporting rates and human population. The Seventh chapter follows a similar pattern with chapter six. However, chapter seven, examines patterns between a socio-economic index, mean income per person, and the reporting rates of birds in Greater Gauteng. The eighth chapter is the conclusion. It gives a synthesis of the thesis and presents the implications for conservation of avian biodiversity in Greater Gauteng. Overall, this thesis highlights the contribution of citizen science can make to research. It also makes for a strong case showing fundamental importance of large volumes of data such as SABAP2 data, and the useful information that can be harnessed from this data. The conservation-relevant studies in the chapters of this thesis are a result of the spatial distribution patterns of the avifauna revealed by SABAP2 data from Greater Gauteng. It showed how we can detect changes in species abundance, richness and composition in a pentad or in any area, a method we can extend further to detect when bird species are starting to decline or drop out of the species list for a pentad. The results reported in this thesis provides a rich field of study for future research, especially in the field of urban ecology.